Experimental Modeling and Optimization of Fatigue Life and Hardness of Carbon Steel CK35 under Dynamic Buckling - Al-Khazraji, Ahmed Naif (Al-Khwarizmi Engineering Journal, 2017)
Abstract The aim of this paper is to model and optimize the fatigue life and hardness of medium carbon steel CK35 subjected to dynamic buckling. Different ranges of shot peening time (STP) and critical points of slenderness ratio which is between the long and intermediate columns, as input factors, were used to obtain their influences on the fatigue life and hardness, as main responses. Experimental measurements of shot peening time and buckling were taken and analyzed using (DESIGN EXPERT 8) experimental design software which was used for modeling and optimization purposes. Mathematical models of responses were obtained and analyzed by ANOVA variance to verify the adequacy of the models. The resultant quadratic models were obtained. A good agreement was found between the results of these models and optimization with the experimental ones with confidence level of 95 %.